Vincristine, Irinotecan, and Temozolomide in Patients With Relapsed/Refractory Neuroblastoma - Zhu, Jia; Wang, Juan; Sun, Feifei; Zhen, Zijun; Chen, Tingting; Lu, Suying; Huang, Junting; Zhang, Yizhuo; Sun, Xiaofei (Frontiers in Oncology, 2022)
Purpose: The combination of irinotecan, temozolomide and vincristine has been proposed as an effective salvage regimen for some pediatric malignancies. Thus, we sought to evaluate this combination for patients with relapsed and refractory neuroblastoma (NB). Patients and Methods: Forty-six patients with relapsed or refractory NB were treated with the combination of vincristine (1.5 mg/m2 i.v. day 1), irinotecan (50 mg/m2 /day i.v. days 1–5) and temozolomide (100 mg/m2 /day p.o. days 1–5) (VIT) during the period 2011–2019. All toxicities were documented. Results: A total of 251 cycles (median 6 cycles/patient) were administered. A complete response (CR) was achieved in 5 patients, partial response (PR) in 27 patients, stable disease (SD) in 8 patients, and progression disease (PD) in 6 patients, with an overall objective response rate (CR+PR) of 69.6%. Eighteen patients developed diarrhea with Grade Ⅲ or less. Grade 1-2 hematologic toxicity occurred in 10 patients. Grade 3-4 hematologic toxicity developed in 32 patients. VIT was an effective regimen for different metastatic sites. UGT1A*28 genotyping performed in 7 patients revealed wild type. Diarrhea occurred in 4 of them. Conclusion: The shorter, 5-day VIT regimen is an active and well-tolerated salvage regimen in relapse/refractory NB.